FAKTOR-FAKTOR YANG MEMENGARUHI PENINGKATAN BELAJAR BAHASA ARAB PADA PERGURUAN TINGGI KEAGAMAAN ISLAM DI INDONESIA - Muhammad Irwan (JUPE : Jurnal Pendidikan Mandala, 2022)
The problems of Arabic learning are the elements that hinder the implementation of successful Arabic learning. The study was created with the aim of revealing the factors that can support Arabic learning skills. The research method used a library research. The data were studied and analyzed until it obtains discussions related to Arabic language learning. The results of this study revealed that the factors that influence the improvement of Arabic learning skills are human resources, namely teaching staff, learning duration, curriculum, physical and financial facilities, as well as language and environmental institutions.